OP0038 Autologous hematopoietic stem cells (hsc) transplantation in scleroderma and myositis. (1st June 2001) - Farge, DC; Zohar, S; Andre, MH; Cabane, J; Hachulla, E; Philippe, P; Sibilia, J; Roblot, P; Piette, J; Chevret, S; Marroleau, JP; Gluckman, E
Abstract : Background: Autologous bone marrow transplant is a new treatment for autoimmune diseases (AD). Objectives: To determine the feasibility, tolerance and efficacy of autologous HSC transplantation with CD34 + selection in severe scleroderma (Sc) and myositis (M). Methods: We designed a national, non randomised, open, phase I-II trial. 1 Mobilisation of HSC used cyclophosphamide (CYCLO) (4 g/m 2 )+ G-CSF (5 microg/kg day) or G-CSF alone (10 microg/kg day) if left ventricular ejection fraction (LVEF) was < 40% until last apheresis. 9.5 × 106 CD34 + /kg had to be collected in successive daily apheresis to obtain at least 2.5 × 106 CD34 + /kg (Isolex ® 300i). Conditioning used CYCLO (200 mg/kg), or melphalan (140 mg/m 2 ) if LVEF was < 40%, prior to CD34 + HSC reinfusion. Patients, haematological and immunological reconstitutions were recorded up to the end of aplasia and every 3 months thereafter. Sequential Bayesian analysis determined the rate of failure (either death or failure of mobilisation, selection or intensification) and results (median) were computed on a SAS program (6.0). Results: 12 Sc + 3 M, age 36 yrs, were included in 2 years, meanwhile 10 candidates died from their disease. HSC mobilisation was successful in 14 patients, but in 2 cases did not yield enough HSC to allow CD34 + selection. After 2 (1–4) aphereses, the total number of CD34 + collected for each patient was 10.9 × 106/kg (3.9?34.3). Purity was 99.2% (92–99.8). CD34 + cells yield was 60.7% (46.4–80). Intensive immunosuppression was performed in 13 patients with low toxicity. Number of reinfused cells was 5.8 × 106 CD34 + /kg (3.3–10.2). Duration of aplasia was 2.9 weeks (2.5–3) with low toxicity. No mortality was associated with the procedure. Early clinical evolution (18 mths) showed improved functional status (PS, SHAQ) and fall in skin score in 8/12 Sc and no clinical benefit in M. Conclusion: Autologous HSC transplantation is feasible in Sc and M, with a lower risk compared to spontaneous evolution of AD and early clinical benefit in Sc. These results call for phase III studies to compare cyclophosphamide alone versus autologous transplantation in Sc and for more myositis in phase I–II studies. Reference: Farge D, Gluckman E, Tyndall A. Treatment of severe autoimmune diseases by immunoablative chemotherapy and autologous bone marrow transplantation. EJIM 1999;10:88–96